Use of Learning Management Systems (LMS) As A Network Learning Media (Online) During the Covid-19 Pandemic - Sumardi, Dody; Suryani, Nunuk; Musadad, Akhmad Arif (Future Science, 2021)
The Covid-19 coronavirus pandemic that has hit the world has now changed the order of human life, every activity uses masks, maintains distance, does not gather, and washes hands. The government does not allow face-to-face learning in the classroom, so learning is carried out online (online), teachers provide learning using several e-learning platforms that are available as long as they are supported by internet facilities. The use of these different platforms resulted in the learning process being less than optimal due to the lack of coordination between teachers, management, and students. Learning scheduling which is carried out individually is not coordinated, this makes it difficult for teachers and students to start learning and is verified/monitored by management to ensure the quality of learning. Students find it difficult to know and repeat the subject matter that has been implemented. This online learning process needs a media that can manage all learning activities starting from planning, implementation to evaluation that makes it easier for management, teachers, and students. The method in this writing is the method of literature from experts and some research results that are descriptive-analytical. LMS media is expected to be able to manage the learning process that begins with scheduling, subject matter and evaluation easily which can be accessed and studied by students online using the LMS. Management can control and monitor the learning process, and parents can also participate in monitoring, following, and directing learning.